Havoline Thermometer
World's Tallest Thermometer - Twenty-one stories (218ft) high. Shows temperature by neon-light tubes. Sponsored by Indian Refining Company, Lawrenceville, Ill., makers of Waxfree Havoline Motor Oil - best for all cars, winter or summer, because it contains no wax. Wax turns candle-hard with cold, water-thin with heat. Keep wax out of your motor! Waxfree Havoline Motor Oil is Sold at all Texaco Stations.